APPLICATION OF PEER TEACHING LEARNING METHOD TO IMPROVE THE ABILITY TO READ THE QUR'AN CLASS IV AT SDN 21 SIJUNJUNG - Fitriawati, Hemnel (State Institute for Islamic Studies Batusangkar, 2020)
This study aims to determine the improvement of students' reading ability of Q.S Al-Fiil with the application of peer teaching methods in class IV SDN 21 Sijunjung. This research method is Classroom Action Research that is: